Five-year outcome of clinical recovery and subjective well-being in older Dutch patients with schizophrenia. (17th October 2021) - Meesters, Paul D.; Lange, Sjors M. M.; Wunderink, Lex; Stek, Max L.; Rhebergen, Didi
ABSTRACT: Outcome of schizophrenia in later life can be evaluated from different perspectives. The recovery concept has moved forward this evaluation, discerning clinical-based and patient-based definitions. Longitudinal data on measures of recovery in older individuals with schizophrenia are scant. This study evaluated the five-year outcome of clinical recovery and subjective well-being in a sample of 73 older Dutch schizophrenia patients (mean age 65.9 years; SD 5.4), employing a catchment-area based design that included both community living and institutionalized patients regardless of the age of onset of their disorder. At baseline (T1), 5.5% of participants qualified for clinical recovery, while at five-year follow-up (T2), this rate was 12.3% ( p = 0.18; exact McNemar's test). Subjective well-being was reported by 20.5% of participants at T1 and by 27.4% at T2 ( p = 0.27; exact McNemar's test). Concurrence of clinical recovery and subjective well-being was exceptional, being present in only one participant (1.4%) at T1 and in two participants (2.7%) at T2. Clinical recovery and subjective well-being were not correlated neither at T1 ( p = 0.82; phi = 0.027) nor at T2 ( p = 0.71; phi = −0.044). There was no significant correlation over time between clinical recovery at T1 and subjective well-being at T2 ( p = 0.30; phi = 0.122) nor between subjective well-being at T1 and clinical recovery at T2 ( p = 0.45; phi = −0.088). These results indicate that while reaching clinical recovery is relatively rare in older individuals with schizophrenia, it is not a prerequisite to experience subjective well-being.